Role of Nhp6 and Hmo1 in SWI/SNF occupancy and nucleosome landscape at gene regulatory regions - Hepp, Matias I. (Biochim Biophys Acta, 2017)
Diverse chromatin modifiers are involved in regulation of gene expression at the level of transcriptional regulation. Among these modifiers are ATP-dependent chromatin remodelers, where the SWI/SNF complex is the founding member. It has been observed that High Mobility Group (HMG) proteins can influence the activity of a number of these chromatin remodelers. In this context, we have previously demonstrated that the yeast HMG proteins Nhp6 and Hmo1 can stimulate SWI/SNF activity. Here, we studied the genome-wide binding patterns of Nhp6, Hmo1 and the SWI/SNF complex, finding that most of gene promoters presenting high occupancy of this complex also display high enrichment of these HMG proteins. Using deletion mutant strains we demonstrate that binding of SWI/SNF is significantly reduced at numerous genomic locations by deletion of NHP6 and/or deletion of HMO1. Moreover, alterations in the nucleosome landscape take place at gene promoters undergoing reduced SWI/SNF binding. Additional analyses show that these effects also correlate with alterations in transcriptional activity. Our results suggest that, besides the ability to stimulate SWI/SNF activity, these HMG proteins are able to assist the loading of this complex onto gene regulatory regions.